2000
DOI: 10.1159/000025453
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of the Nociceptin Receptor, ORL1

Abstract: A novel opioid receptor-like orphan receptor (ORL1) was cloned and identified to be homologous to classical opioid receptors but insensitive to traditional opioids. A heptadecapeptide, termed orphanin FQ or nociceptin (OFQ/N), was identified as its endogenous ligand. OFQ/N shares overlapping distribution sites in pain-processing areas and common cellular mechanisms with opioids but exerts diverse effects on nociceptive responses. Of the two reported ORL1 antagonists, [Phe1ψ(CH2-NH)- Gly Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Naloxone benzoylhydrazone (NalBzOH) had been reported to be an antagonist and agonist, respectively, at μ‐ and κ‐opioid receptors14 before NOP receptors were discovered. It was later found to act as a NOP antagonist in studies in vitro and in vivo 13. In vlPAG neurons, we have found that NalBzOH is a competitive antagonist of NOP receptors that mediate GIRK channel activation with a pA2 value of 5.67 9.…”
Section: Naloxone Benzoylhydrazonementioning
confidence: 69%
See 2 more Smart Citations
“…Naloxone benzoylhydrazone (NalBzOH) had been reported to be an antagonist and agonist, respectively, at μ‐ and κ‐opioid receptors14 before NOP receptors were discovered. It was later found to act as a NOP antagonist in studies in vitro and in vivo 13. In vlPAG neurons, we have found that NalBzOH is a competitive antagonist of NOP receptors that mediate GIRK channel activation with a pA2 value of 5.67 9.…”
Section: Naloxone Benzoylhydrazonementioning
confidence: 69%
“…In vlPAG neurons, we found that it activated GIRK channels, as did N/OFQ, although it antagonized the effect of N/OFQ, that is, acting as a partial agonist at the native NOP receptors of the midbrain PAG 12. Thereafter, several reports also proved that it is a partial agonist of NOP receptors in central and peripheral nervous systems and has intrinsic activity at the NOP receptors involved in nociception as well as cardiovascular and renal functions 6,13…”
Section: [Phe1ψ(ch2‐nh)gly2]n/ofq(1‐13)nh2mentioning
confidence: 74%
See 1 more Smart Citation
“…[Phe 1 (CH 2 -NH)Gly 2 ] nociceptin-(1-13)-NH 2 (Phe ), naloxone benzoylhydrazone (NBZ), acetyl-RYYR1K-NH 2 and nocistatin, have been reported [7], their mode of action remains elusive. Chiou [3] reported that none of the putative ORL1 antagonists as listed above could be considered as specific and potent antagonist for the ORL1 receptors as measured from the inward rectifier activation in the periaqueductal gray neurons. These observations point to the urgent need for the development of a new generation of ORL1 antagonists.…”
Section: Pharmacology Of the Nociceptin Receptormentioning
confidence: 99%